Politics and Pentecostalism in Australia: Prime Minister Morrison as the “Miracle Man” - Austin, Denise A.; Perry, David 1981-; Fogarty, Stephen (2022)
Pentecostalism and politics are, for better or worse, no strangers. In 2018, Scott Morrison became the first pentecostal prime minister in the history of Australia and, possibly, in the English-speaking world. He then led the Liberal Party to a resounding election victory in 2019. As a result, Morrison was dubbed the “Miracle Man” after his acceptance speech referred to divine intervention in the electoral results. Since then, there has been regular, negative speculation on links between Morrison’s pentecostal faith and policy positions. This article provides a counterposition that several elements of the pentecostal worldview have the potential for positive impact in politics and may explain aspects of Morrison’s electoral success. We argue that Morrison effectively leveraged his pentecostal experience and convictions to advantage through strong leadership, practical pragmatism, marketing acumen, and a narrative of hope. Here, in a morass of indecision and “policy-free” political elites, was someone who believed in something.
Keywords: Australian Christian Churches; Pentecostalism; Scott Morrison; Politics; Australia